Les pronoms dans une perspective cognitive - Laure Gardelle (Corela)
The aim of the study is to review how cognitive approaches address the class of pronouns, through a selection of occurrences taken from a set document. In particular, the aim is to see how the treatment of pronouns in cognitive approaches fits into a broader theoretical model of language, and conversely, how the latter has influenced perspectives on the class. The main model considered here is more specifically Langacker’s Cognitive Grammar (CG), with the exception of a development on reference-based approaches. The study first specifies what is meant by a ‘cognitive’ approach, and goes on to establish the shared characteristics of pronouns in the CG framework (schematic specification, associated with grounding for full nominal expressions; referential function, to be distinguished from definiteness). The study then considers the various subclasses of pronouns. Among others, it brings out the central role of personal pronouns (far from the status of impoverished substitute they have in a number of other approaches) and demonstratives; a rejection of transformational syntax (reorganised constituents) in favour of constructions; a rejection of semantically ‘empty’ pronouns; and an extension of the notion of ‘impersonal’ to we or they. The concept of ‘there-cleft’, borrowed from Davidse (2000) and Reeve (2012) rather than CG, is also put forward.